Advances in design for cross-cultural activities. - Schmorrow, Dylan D.; Nicholson, Denise, 1967- (Advances in human factors and ergonomics series., 2013)
"This reference focuses on decision-making styles within cultures. It focuses on cooperative, collaborative, avoidant, competitive, and dominant styles of decision making, and discusses how each process is modified by the culture. The contributors examine issues within culture that affect decision making, such as individualism and collectivism, considered the most important influences in decision making. This reference is one of 10 predicted to be derived from the 2012 Applied Human Factors and Ergonomics (AHFE) Conference"--